Sulforaphane ameliorates amyloid-β-induced inflammatory injury by suppressing the PARP1/SIRT1 pathway in retinal pigment epithelial cells. Issue 1 (1st January 2022) - Wang, Song; Tang, Yu-jie
ABSTRACT: Age-associated macular degeneration (AMD) is a progressive eye disorder that leads to irreversible impairment of central vision, and effective therapies are lacking. Here, we explore how oligomeric amyloid-β1-42 can trigger inflammatory injury in retinal pigment epithelial cells and how sulforaphane can mitigate such injury. ARPE-19 retinal pigment epithelial cells expressing low, endogenous, or high levels of poly(ADP-ribose) polymerase (PARP1) were treated with oligomeric amyloid-β1-42 in the presence or absence of various signaling inhibitors or sulforaphane. Cell viability, apoptosis, inflammatory responses, and activity of the PARP1/Sirtuin (SIRT1) axis were assayed. Treating ARPE-19 cells with oligomeric amyloid-β1-42 promoted the production of IL-1β, IL-6, IL-8, and TNF-ɑ, which was partially reversed by inhibiting PARP1 and activating SIRT1. PARP1 was found to act upstream of SIRT1, and expression of the two proteins correlated negatively with each other. Sulforaphane also mitigated the injury due to oligomeric amyloid-β1-42 through a mechanism involving inactivation of the PARP1/SIRT1 pathway. Oligomeric amyloid-β1-42 can trigger AMD-like injury in retinal pigment epithelium by activating PARP1 and repressing SIRT1. Moreover, sulforaphane can induce cell viability and SIRT1 expression, but reduce cell apoptosis, the activity of caspase-3 or −9, and PARP1 expression in oAβ1-42 -treated cells. However, PARP1 inactivation or SIRT1 activation weaken these effects. In summary, sulforaphane reduces the inflammatory injury induced by oAβ1-42 in ARPE-19 cell by inactivating the PARP1/SIRT1 pathway. Thus, the compound may be an effective therapy against AMD.